2014
DOI: 10.1124/jpet.114.214155
|View full text |Cite
|
Sign up to set email alerts
|

GSK356278, a Potent, Selective, Brain-Penetrant Phosphodiesterase 4 Inhibitor That Demonstrates Anxiolytic and Cognition-Enhancing Effects without Inducing Side Effects in Preclinical Species

Abstract: Small molecule phosphodiesterase (PDE) 4 inhibitors have long been known to show therapeutic benefit in various preclinical models of psychiatric and neurologic diseases because of their ability to elevate cAMP in various cell types of the central nervous system. Despite the registration of the first PDE4 inhibitor, roflumilast, for the treatment of chronic obstructive pulmonary disease, the therapeutic potential of PDE4 inhibitors in neurologic diseases has never been fulfilled in the clinic due to severe dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…All these subtypes are selective for cAMP (Rutter et al, 2014). In the present study, the authors have demonstrated the subtype -specific inhibitory properties of rolipram and roflumilast on PDE-4, of which PDE-4B and PDE-4D were significantly inhibited.…”
Section: Discussionmentioning
confidence: 68%
“…All these subtypes are selective for cAMP (Rutter et al, 2014). In the present study, the authors have demonstrated the subtype -specific inhibitory properties of rolipram and roflumilast on PDE-4, of which PDE-4B and PDE-4D were significantly inhibited.…”
Section: Discussionmentioning
confidence: 68%
“…There has been no clinical data to show the improvement of cognition by PDE4 inhibitors in clinical settings although several lines of research using animal models suggest that PDE4 inhibition could improve some cognitive domains such as executive functions and memory [32,33]. Regarding PDE4 subtypes, PDE4D is considered to be related to cognitive improvement [34,35] while PDE4B is also considered to be involved in the cognitive function [36].…”
Section: Discussionmentioning
confidence: 99%
“…PDE4 (A to D) inhibitors are used in the therapy of neurological disorders because of their anti-depressant and cognition enhancing effects, mediated by the elevation of intracellular cAMP and increased production of norepinephrine [22]. According to the similarity in phenotype associations between disorders (Fig.…”
Section: Inference Of Novel Gene-and Drug-disorder Associationsmentioning
confidence: 99%